Detection of VRE: VanA and vanB genes by PCR - Merlino, J.; Kay, I.; Coombs, Geoffrey; Palladino, S. (Springer Netherlands, 2010)
In clinical laboratories the phenotypic detection of low-level vancomycin resistance in enterococci is problematic. Rapid detection of vancomycin resistant enterococci (VRE), in particular those that carry the vanA or vanB genes, may minimize transmission within a hospital and therefore reduce the risk of colonization and infection. © 2010 Springer Science+Business Media B.V.